AGENT BASED ACCESS TO HETEROGENEOUS DATABASES - Pysmennyi, Vyacheslav Y.; Ternovoy, Maksym Y. (International Journal of Computing, 2011)
The paper presents the implementation of system for access to the information in distributed information- telecommunication environment with heterogeneous databases using multi-agent approach. Different ways for multi- agent system construction were considered. It was developed a scheme of interaction between agents in the proposed system. The approach aims to improve the efficiency of data access in heterogeneous information systems without the necessity to change them.